The Book of Knowledge: A Pictorial Treasury of Reading & Reference for Young and Old: Volume 4: Geo-Lin - Gordon Stowell (UK The Waverley Book Company Ltd., 1959)
To Inspire Ambition to Stimulate the Imagination. to Provide the Inquiring Mind with Accurate Information Told in An Interesting Style of Thus Lead Into Broader Fields of Knowledge- Such Is the Purpose of This Book
Arranged Alphabetically with Over 7000 Pictures and Diagrams, Including Hundreds in Colour and Gravure
J. Edward Mason Advisory Editor
Keywords: Encyclopedias (3GdehShYGJs; General